The results of breeding work with the winter bread wheat for non-fallow forecrops in the Agricultural Research Center “Donskoy” - D. M. Marchenko; M. M. Ivanisov; I. A. Rybas’; E. I. Nekrasov; I. V. Romanyukina; Yu. Yu. Chukhnenko (Зерновое хозяйство России)
The breeding work with the winter bread wheat in the Federal State Budgetary Scientific Institution “Agricultural Research Center “Donskoy” is being carried out taking into account the increasing aridity of the local climate, the availability of different soil and climatic zones, various forecrops. Every year in the Rostov region there is an increase in the sown area under winter wheat. So, in 2020 the grain crop was sown on more than 2.6 million hectares. Most of it is sown after such non-fallow forecrops as peas, maize, sunflower and other crops. In this regard, it is important to develop and introduce into production winter bread wheat varieties based according to these forecrops. The laboratory for breeding and seed production of winter bread wheat of half-intensive type was established in 1978. For the period from 1978 to 2019, 36 varieties were developed in the laboratory and sent to the State Variety Testing. The main task of the crop breeding for non-fallow forecrops was and still remains to develop highly productive varieties with high frost resistance, drought resistance, heat resistance, resistance to major diseases and grain quality of strong and valuable wheat. In 2020 22 winter bread wheat varieties, developed in the laboratory, have been included into the State List of Breeding Achievements of the Russian Federation. Currently five winter bread wheat varieties ‘Polina’, ‘Ambar’, ‘Niva Dona’, ‘Podarok Krymu’ and ‘Premiera’ are undergoing the State Variety Testing. There is still going on the work on the development of new winter bread wheat varieties that meet modern production requirements, with a wide ecological adaptability and stability of productivity and quality of grain and flour.